Opisa takafuminakanoi, a new species of Opisidae from Hokkaido, Japan (Crustacea: Amphipoda) - Narahara-Nakano, Yukiko; Kakui, Keiichi; Tomikawa, Ko (Zootaxa, 2016)
Opisa is a small amphipod genus including three species: O. eschrichtii (Krøyer, 1842) from the North Atlantic Ocean (Sars 1895; Bousfield 1987), the Arctic Ocean (Bousfield 1987), and the western Pacific Ocean (Stebbing 1906; Derzhavin 1929); O. odontochela Bousfield, 1987 from the southeast Alaska (Bousfield 1987); and O. tridentata Hurley, 1963 from the Pacific coasts of North America (Bousfield 1987). During field survey of the marine benthic fauna of Hokkaido, Japan, one of the authors (KK) collected an undescribed species of Opisa from off the southeast of Akkeshi Bay using a sledge net. This paper describes and illustrates the new species in detail.